?HYPOTENSIVE ACTION OF AN EXTRACT OF HIBISCUS ROSA SINENSIS, LINN - Ahmed, Shahnaz; Qureshi, Shamim; Mirza, Maryam; Qadri, Naseem M; Bukhari, A Q S (Biological Sciences - PJSIR, 2001)
Hypotensive action of extract of pink flowers of Hibiscus rosa sinensis, Linn. was investigated in rats and dogs: It was foundthat45 mgkg’ ofan aqueousextractofpinkflowers loweredthebloodpressureofratsfrom 80 mmHg to40 mmHg while adose of60 mgkg ’ of sameextract produceda fallinblood pressureofdogsfrom 120 mmHgto40 mmHg, butthe duration of hypotensive action was more than 3-4 h in both thecases i.e. rats and dogs. Also the biphasic response of the drug and its possible mode of action is discussed.